1645 Vancomycin in Newborns: Comparison of a Standard dose to Dosing Adjusted for Birth Gestation and Age. (October 2012) - Duffy, D; Gayfieva, M; Thomson, MA
Abstract : Background: Vancomycin dosing regimens and individual pharmacokinetics vary in newborns. A time lag in achieving therapeutic levels often occurs with delays in treating sepsis or toxicity. Aims: To investigate initial therapeutic trough levels (10–15 mg/l) achieved by a standard dose (15mg/kg/dose 12 hourly) for all newborns compared to new dosing accounting for birth gestation and postnatal age. 1 Methods: Admissions from March 2010- January 2012 were included. Data on gestation, age, initial therapeutic level (pre 4 th dose) and creatinine were analysed. Results: 111 treatment courses in 83 infants were evaluated. The new dosing increased the proportion of therapeutic levels [18/68 (26%) vs.16/43 (37%), p=0.29], greatest in infants ≥ 29 weeks at birth, ≥ 10 days old (12% vs. 66%). Toxicity decreased [21/68 (31%) vs. 9/43 (21%), p=0.28]. Sub-therapeutic levels were unchanged (40% vs. 43%). Creatinine was higher with toxic levels compared to therapeutic/low levels (p<0.0001). No infants with creatinine < 100 umol/l had toxic levels. 18/27 (66%) with toxic levels had a creatinine of > 100 umol/l. Conclusions: Dosing accounting for birth gestation and age resulted in a greater proportion of therapeutic levels and less toxicity but sub-therapeutic levels remain frequent. We recommend large scale population studies to determine the optimal dosing strategy. Reference: Wallis, Williamson. Arch Dis Child F&N 2011; 96. < 29 weeks at birth : < 10 days: 20mg/kg 18 hourly; > 10 days: 15mg/kg 12 hourly. ≥ 29 weeks at birth: < 10 days: 15mg/kg 12 hourly; > 10 days: 15 mg/kg 8 hourly.